Pengetahuan Keuangan dan Kepribadian Berkontribusi dalam Membentuk Perilaku Keuangan Berkelanjutan - Mita Anzaningtyas; Khusaini Khusaini; Sri Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to investigate the impact of financial knowledge and personality on people's sustainable financial behavior. Researchers utilized a cross-sectional survey approach. The target population of the study was people aged 18-59 years in Kutabumi Village, Pasar Kemis Subdistrict, Tangerang Regency, amounting to 10,852 people. The researcher determined a sample size of 386 participants (Slovin formula, sampling error 5%) using proportionate stratified random sampling technique. Each participant was given a questionnaire that had been validated by validity and reliability tests. The questionnaire was distributed through WhatsApp groups. The binary logit estimation results showed that financial knowledge had a positive and significant impact on sustainable financial behavior, as well as personality. In other words, the more people's knowledge increased and the better their personality, the probability of improving sustainable financial behavior increased. Thus, financial decisions taken by the community consider future circumstances. The empirical implication of this research is the importance of emphasizing basic financial knowledge in long-term financial knowledge planning education and improving personality for better financial behavior.